Internal and External Key Success Factors of Business Process Re-Engineering (BPR): Effects on the Islamic Banks Performance - Razalli, Mohd Rizal; Hasnan, Norlena; Sin, Mohammad Aizat Md (International Journal of Engineering and Technology, 2018)
Objective: The purpose of this study is to determine causal relationship between internal and external factors of Business Process Reengineering (BPR) and the performance of Islamic banks in Malaysia.Methodology: The questionnaires were distributed and collected in the Bank Headquarters (HQs). From 64 sets of questionnaires, only 42 sets were returned and only 35 sets were usable for further analysis after the data screening process. PLS analysis was conducted to examine the causal relationship between the internal and external factors and organizational performance.Results: The result showed that the internal factor had a significant effect on the performance of the Islamic banks, while external factor had no significant effect to these bank’s performance.Implication: The findings of this study provides important insights for Islamic financial institutions and researchers in the area of Islamic banking performance and business process reengineering projects.